ARTIFICIAL SWEETENERS AND BODY WEIGHT: A CRITICAL REVIEW OF CURRENT EVIDENCE - Lidia Jurczenko; Ewa Szczęsna; Marta Miejska-Kamińska; Izabella Sośniak (International Journal of Innovative Technologies in Social Science, 2025)
Artificial sweeteners (AS), or non-nutritive sweeteners, are widely promoted as sugar substitutes for weight management. Their use is based on the assumption that they lower caloric intake and improve metabolic outcomes, yet the evidence remains conflicting. This review synthesizes findings from randomized controlled trials (RCTs), preclinical models, observational studies, and mechanistic research.Meta-analyses of RCTs demonstrate modest benefits, with mean reductions of −0.8 kg in body weight and −0.24 kg/m² in BMI. These effects are most evident in short-term interventions, while long-term trials generally report no sustained advantage over sugar or placebo. Preclinical data are heterogeneous: chronic AS exposure in obesity-prone rodents often promotes weight gain and metabolic dysregulation, whereas benefits are observed when AS replace sucrose in energy-restricted conditions.Epidemiological studies associate AS intake with increased risks of obesity (OR ≈ 1.5), type 2 diabetes (OR ≈ 3.7), and hypertension (OR ≈ 1.5). Although residual confounding and reverse causality cannot be excluded, these findings raise concerns about adverse long-term outcomes. Mechanistic studies suggest that AS may alter gut microbiota, impair satiety signaling, and promote compensatory feeding, with additional effects on insulin sensitivity and reward pathways.In summary, AS confer limited short-term benefits and uncertain long-term efficacy in weight control. Concerns raised by observational and mechanistic data support the World Health Organization’s recommendation against their routine use. Future research should clarify sweetener-specific effects, interindividual variability, and long-term outcomes to inform dietary guidelines and public health strategies.